Effects of different soil amendments on physicochemical property of soda saline-alkali soil and crop yield in Northeast China - Xiao, Fan; Zhou, Beibei; Wang, Hongbin; Duan, Manli; Feng, Lei (International Journal of Agricultural and Biological Engineering, 2022)
Soil amendment is one of the most effective methods to improve saline-alkali soil. In this study, laboratory experiments were conducted to verify the effect of 13 kinds of amendments and their combinations (Citric acid (NM), Phosphogypsum (LS), Aluminum sulfate+citric acid (AL+NM), Aluminum sulfate+phosphogypsum (AL+LS), Aluminum sulfate+citric acid+phosphogypsum (HH), Zeolite (Z), Acidified zeolite (ZH), Aluminum sulfate (AL), Aluminum sulfate+zeolite (AL+Z), Aluminum sulfate+acidified zeolite (AL+ZH), Poly Aluminum chloride (ALCL), Polyaluminium chloride+zeolite (ALCL+Z), Polyaluminium chloride+acidified zeolite (ALCL+ZH)) on soil pH, metal cations content, exchangeable Na+, exchangeable sodium percentage (ESP) in the lab. And then the five most effective amendments (Z, ZH, AL, AL+Z, and AL+ZH) were chosen applying both in dry field (maize field) and paddy field to evaluate their improvement on soda saline-alkali soil and crop yield in the northeast Songnen Plain, China. The lab results showed that AL, AL+Z and AL+ZH treatments could significantly reduce the pH in soil solution and increase the content of metal cations. Z and ZH treatments could adsorb metal cations in soil. Both in dry and paddy fields, all five treatments could increase the soil saturated hydraulic conductivity (Ks), increased from 9.63 to 60.02 mm/d and 0.18 to 33.25 mm/d, respectively, of which the AL treatment was the best; all five treatments could reduce the content of exchangeable Na+ in soil, and decrease by 38.62%-61.33% and 25.24%-71.53%, respectively, of which the AL+ZH treatment was the best; all treatments could reduce soil exchangeable sodium percentage, and decrease by 0.14-0.22 and 0.14-0.41, respectively, of which the AL+ZH treatment was the best; AL, AL+Z and AL+ZH treatments could improve soil organic matter content; all treatments could effectively improve the yield of crops, and increase 23.98%-60.75% and 52.51%-260.21%, respectively, of which the AL treatment was the best in dry field and the AL+ZH treatment was the best in paddy field. The effect of AL treatment was the best in dry field and AL+ZH treatment was the best in paddy field of soda saline-alkali soil. This study could provide instructive information for the chemical improvement and agricultural utilization of soda saline-alkali soils in the world. Keywords: soil amendments, soda saline-alkali soil, aluminum sulfate, zeolite, maize, rice DOI: 10.25165/j.ijabe.20221501.6252 Citation: Xiao F, Zhou B B, Wang H B, Duan M L, Feng L. Effects of different soil amendments on physicochemical property of soda saline-alkali soil and crop yield in Northeast China. Int J Agric & Biol Eng, 2022; 15(1): 192–198.